2000
DOI: 10.1262/jrd.46.157
|View full text |Cite
|
Sign up to set email alerts
|

Time Series Analysis of Plasma Insulin-like Growth Factor-I and Gonadal Steroids in Adolescent lapanese Macaques (Macaca fuscata).

Abstract: Abstract. The present study was conducted to reveal the developmental changes in plasma IGF-1 concentrations in male and female Japanese macaques by a long-term longitudinal method from 3 to 6 years of age. The sexual maturation and reproductive seasonality in both genders were determined by plasma profiles of gonadal steroids, such as testosterone and progesterone. Since Japanese macaques have been known to have a rather unique characteristic of clear seasonality in reproduction, the present study introduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…This is because gibbons do not show such remarkable morphological changes with reproductive maturation like macaques or chimpanzees (e.g., swelling of sexual skin). Our previous study revealed a close functional relationship between insulin-like growth factor-1 (IGF-1) and skeletal growth in Japanese macaques (Macaca fuscata) (Suzuki et al 2000). We also confirmed that the adolescent phase of the macaque males begins in the summer at 3 years of age, as shown from the profiles of IGF-1 and testosterone secretion (Suzuki et al 2000).…”
Section: Introductionsupporting
confidence: 77%
See 3 more Smart Citations
“…This is because gibbons do not show such remarkable morphological changes with reproductive maturation like macaques or chimpanzees (e.g., swelling of sexual skin). Our previous study revealed a close functional relationship between insulin-like growth factor-1 (IGF-1) and skeletal growth in Japanese macaques (Macaca fuscata) (Suzuki et al 2000). We also confirmed that the adolescent phase of the macaque males begins in the summer at 3 years of age, as shown from the profiles of IGF-1 and testosterone secretion (Suzuki et al 2000).…”
Section: Introductionsupporting
confidence: 77%
“…Detailed procedures have been reported previously (Suzuki et al 2000). All samples were determined in duplicate.…”
Section: Hormone Assaysmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental work in captive rhesus macaques demonstrates a seasonal infradian rhythmicity in GH and IGF-I secretion in individuals housed outdoors; compared to females living indoors, outdoor-living females are delayed in skeletal growth due to these endocrine differences [32]. In seasonally reproducing Japanese macaques (e.g., Macaca fuscata [33]), close associations between skeletal growth and body weight are seen in males, but not females. In female macaques, high-fat diets modify GH and IGF levels, apparently accelerating ovulation without a concomitant effect on somatic growth during puberty [34].…”
Section: Gh-igf Axis and Growthmentioning
confidence: 99%